ANALISIS PENGGUNAAN MEDIA SOSIAL DALAM MENDUKUNG PRESTASI AKADEMIK MAHASISWA - Fitriani, Wina; Mutia, Khoilatul; Pramesti, Peronika Regista; Rani, Rani; Nuraliza, Yesa (Ekonis: Jurnal Ekonomi dan Bisnis, 2025)
Abstract: This study analyzes the effect of social media use on student academic achievement, social media has the potential to support learning, such as through access to information, group discussions, and online collaboration. The purpose of this study is to identify patterns of social media use by students, its impact on academic achievement, and factors that encourage its use for academic activities. The results showed that productive use of social media can improve understanding of material, broaden horizons, and facilitate collaboration. However, excessive or undirected use can risk reducing the quality of learning and affecting academic performance. Recommendations from this study include better time management, integration of social media in learning, and policies from educational institutions to optimize the benefits of social media without ignoring its potential negative impacts.Keywords: Social Media, Academic Achievement, Impacts